Affinity maturation and characterization of novel binders to the HIV-1 TAR element based on the U1A RNA recognition motif - Crawford, David W., author; McNaughton, Brian, advisor; Ackerson, Christopher, committee member; Ross, Eric, committee member; Bedinger, Patricia, committee member (Colorado State University. Libraries, 2018)
The increased understanding of the importance of RNA, both as a carrier of information and as a functional molecule, has led to a greater demand for the ability to target specific RNAs, but the limited chemical diversity of RNA makes this challenging. This thesis documents the use of yeast display to perform affinity maturation for the ability of a protein to bind the TAR element of HIV-1, which is a desirable therapeutic target due to its prominent role in the HIV-1 infection cycle. To accomplish this, we used a "semi-design" strategy—repurposing a natural RNA bind- ing protein to bind a different target—by creating a library based on important binding regions (especially the β2β3 loop) of the U1A RRM. Following selection for TAR binding, a strong consensus sequence in the β2β3 loop emerged. The affinity of certain library members for TAR was measured by ELISA and SPR, and it was determined that the best binder (TBP 6.7) had remarkable affinity (KD = ~500 pM). This TAR binding protein also proved capable of disrupting the Tat–TAR interaction (necessary for HIV-1 replication) both in vitro and in the context of extracellular transcription. Through collaboration, we were able to obtain a co-crystal structure of TBP 6.7 and TAR. This crystal structure showed that the overall structure of TBP 6.7 was largely unchanged from that of U1A, thereby validating our semi-design strategy. We also found that the β2β3 loop played a disproportionately large role in the binding interaction (~2⁄3 of the buried surface area). The importance of this region inspired the creation and characterization of peptide derivatives of the TBP 6.7 β2β3 loop. These β2β3 loop derived peptides maintain affinity for TAR RNA (KD = ~1.8 μM), and can disrupt Tat/TAR-dependent transcription. Ultimately, the project has yielded the most avid known binders of TAR RNA, a potential novel platform of TAR binding peptides, and a crystal structure which will hopefully inform future targeting efforts.
Zip file contains data file.
Keywords: protein engineering; RRM; U1A; affinity maturation; TAR; RNA